Strategi Kepala Madrasah dalam Meningkatkan Prestasi Siswa di MTs Muhammadiyah Sumani - Deslina Kudriati (Pendidikan Biologi FKIP UMMY, 2022)
The Strategy of the Head of Madrasa in Developing Student Achievement at Mts Muhammadiyah Sumani. Islamic Education Management Study Program Postgraduate Program at State Islamic University Mahmud Yunus Batusangkar. Thus, this study aims to find out how the madrasa principal's strategy in improving achievement at MTs Muhammadiyah Sumani and to find out what factors that influence the improvement of student achievement data at MTs Muhammadiyah Sumani. This field research uses a case study approach with a qualitative method. Sources of primary data and secondary data of this study are the results of interviews with the head of the madrasa, deputy head, head of administration and teachers as well as supporting documents related to the principal's strategy. Both data were obtained using interview and documentation techniques. Furthermore, the data is reduced, verified and concluded as the output of this study. The results of this study indicate that the principal's strategy in improving students' academic and non-academic achievements is by mixing leadership styles, instilling disciplined attitudes, conducting counselling guidance as a form of advice and motivation by the madrasah principal so that the talents possessed by students can develop, giving appreciation such as rewards for students who excel and provide full support in carrying out their duties as leaders. As the head of MTs Muhammadiyah Sumani has a responsibility in developing and motivating as a motivator. Encouragement and reward are two sources of motivation that are effectively applied by madrasah principals. The success of an organization is influenced by various factors, both internal and environmental factors. Therefore, to improve student achievement, principals need to pay attention to students' motivation and other influencing factors.